2018
DOI: 10.3168/jds.2018-14894
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exogenous glucose infusion on early embryonic development in lactating dairy cows

Abstract: The objective of this study was to examine the effect of intravenous infusion of glucose on early embryonic development in lactating dairy cows. Nonpregnant, lactating dairy cows (n = 12) were enrolled in the study (276 ± 17 d in milk). On d 7 after a synchronized estrus, cows were randomly assigned to receive an intravenous infusion of either 750 g/d of exogenous glucose (GLUC; 78 mL/h of 40% glucose wt/vol) or saline (CTRL; 78 mL/h of 0.9% saline solution). The infusion period lasted 7 d and cows were confin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 46 publications
(54 reference statements)
1
14
0
1
Order By: Relevance
“…Interestingly, in a recent study from our group, glucose infusion into late lactation dairy cows from days 7 to 14 post estrus had an adverse impact on early embryonic development; transfer of day 7 blastocysts to lactating dairy cows reduced mean conceptus length, width, and area on day 14. In addition, a greater proportion of embryos in the control group had elongated to >16 mm in length compared to the glucose infused group [68]. Considering the importance of glucose during development of the ovine conceptus, investigation of intrauterine glucose concentrations during elongation of the bovine conceptus may have practical implications.…”
Section: Slc Transportersmentioning
confidence: 99%
“…Interestingly, in a recent study from our group, glucose infusion into late lactation dairy cows from days 7 to 14 post estrus had an adverse impact on early embryonic development; transfer of day 7 blastocysts to lactating dairy cows reduced mean conceptus length, width, and area on day 14. In addition, a greater proportion of embryos in the control group had elongated to >16 mm in length compared to the glucose infused group [68]. Considering the importance of glucose during development of the ovine conceptus, investigation of intrauterine glucose concentrations during elongation of the bovine conceptus may have practical implications.…”
Section: Slc Transportersmentioning
confidence: 99%
“…Whilst the amino acid 1520 , carbohydrate 2023 and lipid 2,24,25 composition of bovine uterine luminal fluid (ULF) has been interrogated to some degree, analyses extending to additional biochemicals ( e.g . nucleotide, cofactor and vitamin, xenobiotic, peptide, and energy metabolites) have received very little attention, if any, despite their known importance to, and/or potential impact on, central cellular processes.…”
Section: Introductionmentioning
confidence: 99%
“…First, the relationship between plasma glucose and uterine luminal fluid glucose levels is not known; Leane et al (2018) detected no difference in uterine luminal fluid glucose levels between the glucose infusion and control (saline infusion) groups. Second, the baseline plasma glucose levels of lactating cows in this study were already at the higher level reported for heifers or nonlactating cows in previous studies (Maillo et al, 2012;Garverick et al, 2013;Forde et al, 2016), suggesting that the glucose infusion that increased levels by ~10 mg/dL in Leane et al (2018) did not really address an insufficiency. Irrespective, it remains quite surprising that glucose infusion did not affect plasma insulin and nonesterified fatty acids, as could be anticipated in late-lactating dairy cows.…”
mentioning
confidence: 95%
“…Moreover, dairy heifers have inherently higher plasma glucose than high-yielding dairy cows and lower embryonic mortality (Rizos et al, 2010). In a recent publication, Leane et al (2018) asked whether increasing plasma glucose by intravenous supplementation could improve fertility in late-lactating dairy cows (Leane et al, 2018). They describe changes in conceptus development following a constant intravenous glucose infusion for 1 wk after embryo transfer.…”
mentioning
confidence: 99%
See 1 more Smart Citation